The story I tell myself : a venture in existentialist autobiography - Barnes, Hazel Estella (University of Chicago Press, 1998)
The Story I Tell Myself is an engrossing account of one woman's psychological liberation from a false sense of what she wanted to be, and of the gradual development of a personal philosophy she was willing to live by. Before she finished college, Barnes had shed her religious beliefs, but she kept intact her inbred convictions that life was difficult, that she was accountable for what she made of her life, and that her actions should accord with her own values. She came of age in the era between Virginia Woolf and Betty Friedan, when women were beginning to break away from traditional patterns but primarily as exceptions and only within limits. Barnes recounts how she came to undertake the translation of Sartre and the subsequent battles with publishers and some hostile critics. Taking to heart Sartre's belief that an individual is both the product and the unique expression of his or her period, Barnes describes how she made Existentialism her own - introducing it in writing, in speaking, and in a television series.